Applying Bim and Related Technologies for Maintenance and Quality Management of Construction Assets in Vietnam - To, Thi Huong Quynh; Phuong, Luu Quang; Nam, Le Hoai (International Journal of Sustainable Construction Engineering and Technology, 2022)
Maintenance and quality management is an important task that aims to maintain the quality and performance of a construction asset under its design and requirements, to ensure the safety and the needs of its owner(s) and user(s). However, in reality, the uniqueness and complexity of construction assets along with the diversity of stakeholders involved are significant challenges that make the maintenance has not achieved the desired effect and goals, thus affect the construction assets quality. The paper studies application of Building Information Modelling (BIM), and related technologies such as Barcode, Radio Frequency Identification (RFID), Sensor, Internet of Things (IoT), Augmented Reality (AR) in many countries around the world; accompany with investigating into the readiness of these technologies in Vietnam. The study results show that all these technologies are available on the market in Vietnam. However, the technology readiness of the maintenance unit is narrow and needs to be improved. The study findings of the benefits and challenges of advanced technology adoption and the ability to implement them in Vietnam provide reliable ascertainment for researchers and construction asset managers in promoting the application of digital technologies to improve the quality and effectiveness of maintenance and quality management of construction assets in Vietnam